The effects of probiotic and selenium co-supplementation on parameters of mental health, hormonal profiles, and biomarkers of inflammation and oxidative stress in women with polycystic ovary syndrome - Mehri Jamilian; Shirin Mansury; Fereshteh Bahmani; Zahra Heidar; Elaheh Amirani; Zatollah Asemi (BMC, 2018)
Abstract Background The aim of this study was to evaluate the effect of the co-administration of probiotic and selenium on parameters of mental health, hormonal profiles, and biomarkers of inflammation and oxidative stress in women with PCOS. Data on the effects of selenium and probiotic co-supplementation on mental health, hormonal and inflammatory parameters of patients with polycystic ovary syndrome (PCOS) are scarce. This investigation was carried out to evaluate the effects of selenium and probiotic co-supplementation on mental health, hormonal and inflammatory parameters in women with PCOS. Methods This randomized, double-blinded, placebo-controlled clinical trial was conducted on 60 subjects, aged 18-40 years old. Participants were randomly allocated into two groups to intake 8 × 109 CFU/day probiotic plus 200 μg/day selenium supplements (n = 30) or placebo (n = 30) for 12 weeks. Hormonal and inflammatory parameters were measured at baseline and after the 12-week intervention. Results Probiotic and selenium co-supplementation resulted in a significant improvement in beck depression inventory (β − 0.76; 95% CI, − 1.26, − 0.26; P = 0.003), general health questionnaire scores (β − 1.15; 95% CI, − 1.97, − 0.32; P = 0.007) and depression anxiety and stress scale scores (β − 1.49; 95% CI, − 2.59, − 0.39; P = 0.009) compared with the placebo. Furthermore, probiotic and selenium co-supplementation significantly reduced total testosterone (β − 0.26 ng/mL; 95% CI, − 0.51, − 0.02; P = 0.03), hirsutism (β − 0.43; 95% CI, − 0.74, − 0.11; P = 0.008), high-sensitivity C-reactive protein (hs-CRP) (β − 0.58 mg/L; 95% CI, − 0.97, − 0.19; P = 0.004) and malondialdehyde (MDA) levels (β − 0.29 μmol/L; 95% CI, − 0.56, − 0.02; P = 0.03), and significantly increased total antioxidant capacity (TAC) (β + 84.76 mmol/L; 95% CI, + 48.08, + 121.44; P < 0.001) and total glutathione (GSH) levels (β + 26.78 μmol/L; 95% CI, + 4.33, + 49.23; P = 0.02) compared with the placebo. Conclusions Overall, the co-administration of probiotic and selenium for 12 weeks to women with PCOS had beneficial effects on mental health parameters, serum total testosterone, hirsutism, hs-CRP, TAC, GSH and MDA levels. This study was prospectively registered in the Iranian website (www.irct.ir) for registration of clinical trials (http://www.irct.ir: IRCT20170513033941N22). Trial registration IRCT20170513033941N22.